Investigating on-call work in rail infrastructure maintenance - Cebola, Nuno M.F. (2014)
The use of on-call work in industry has now surpassed that of shiftwork and night work. Industries as a whole make use of on-call work daily as a way to maintain 24/7 operations whilst also reducing costs. Despite this, on-call work remains underresearched and no best practice or management guidelines are available. As the first substantial piece of human factors work examining on-call work in the rail industry, this thesis has the overall aim of increasing the understanding of on-call scheduling systems of work, and also to provide recommendations to the planning and management of on-call work in the rail industry which may also be applied in other industries.